STABILISASI TANAH LEMPUNG DENGAN SEMEN SEBAGAI STABILISATOR TERHADAP KUAT GESER TANAH PADA SUBGRADE - Muthia Anggraini; Virgo Trisep Haris; Sri Wahyuni (Racic : Rab Construction Research, 2025)
Clay soil is categorized as problematic soil because it has high water content, which causes the soil's shear strength to decrease during rainfall, resulting in low soil bearing capacity. This condition causes damage to structures built on top of it. Soil stabilization is one aspect of soil improvement. Proper soil improvement is necessary to assess soil performance to meet post-construction stability requirements. Chemical stabilization using cementitious materials can improve the engineering properties of expansive soils. The purpose of this study is to analyze the shear strength of cement-stabilized clay soil. Expansive soil is stabilized with cement at variations of 10, 12, 14, and 16% cement by weight. The method used was laboratory testing, consisting of three types of tests: physical soil testing to obtain soil classification, compaction testing to obtain optimum moisture content, and direct shear testing to obtain shear strength values. All tests used Indonesian National Standard (SNI) procedures. The results showed that adding varying amounts of cement resulted in an increase in shear stress values. The maximum value occurred in clay soil stabilized with 14% cement.